Economic determinants of intimate partner violence: The case of Sweden during Covid-19 - Maria Perrotta Berlin; Manne Gerrell (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2022)
We document an increase in intimate partner violence (IPV) against women in Sweden during the first wave of the Covid-19 pandemic, notwithstanding the famously lasseiz-faire approach taken by the coutry. We investigate the role of different mediating factors, affected by the pandemic, by the containment policies, or by their economic consequences, and spilling over to violence incidence, connecting to established theories of violence. We find support for the importance of time spent at home and female unemployment. We also find a positive correlation with alcohol sales.
Keywords: J12; J16; K14; 330; COVID-19; domestic violence; unemployment; self-incapacitation